The Effect of Cross Cultural Understanding (CCU) Subject Toward The Students’ Mindset (A Study on the Sixth Semester Students of English Study Program of FKIP UNTAN Pontianak in Academic Year 2008/2009) - Eni Rosnija; Yenny Suharyanti (Jurnal Visi Ilmu Pendidikan, 2015)
The main purpose of this research is to investigate how far is the effect of Cross Cultural Understanding (CCU) subject toward the students’ mindset. This research also focus on the effect of Cross Cultural Understanding (CCU) subject toward the students’ mindset on the concept of family, education, friendship, time and space. This research is descriptive method. The sample of this research is class A of the sixth semester students of English Study Program of FKIP UNTAN Pontianak in academic year 2008/2009 which consist of 24 students, and the sample is taken by random sampling. The data in this research have been collected by indirect technique through questionnaire. From the result of data analysis, the mean score of the effect of Cross Cultural Understanding (CCU) subject is 116.75 which qualified high effect, it means Cross Cultural Understanding (CCU) subject has high effect toward the students’ mindset. In the concept of family, Cross Cultural Understanding (CCU) subject has very high effect toward the mindset of 2 students, high effect toward the mindset of 7 students, moderate effect toward the mindset of 10 students, and low effect toward the mindset of 5 students. In the concept of education, Cross Cultural Understanding (CCU) subject has very high effect toward the mindset of 12 students, high effect toward the mindset of 11 students, and moderate effect toward the mindset of 1 students.In the concept of friendship, Cross Cultural Understanding (CCU) subject has very high effect toward the mindset of 2 students, high effect toward the mindset of 16 students, and moderate effect toward the mindset of 6 students. In the concept of time, Cross Cultural Understanding (CCU) subject has very high effect toward the mindset of 18 students, and high effect toward the mindset of 6 students.In the concept of space, Cross Cultural Understanding (CCU) subject has very high effect toward the mindset of 5 students, high effect toward the mindset of 16 students, and moderate effect toward the mindset of 3 students. Based on the analysis, there is a positive effect, which is generally qualified in the level of high effect of Cross Cultural Understanding (CCU) subject toward the students’ mindset.